The human obese (OB) gene: RNA expression pattern and mapping on the physical, cytogenetic, and genetic maps of chromosome 7. - Green, E D; Maffei, M; Braden, V V; Proenca, R; DeSilva, U; Zhang, Y; Chua, S C; Leibel, R L; Weissenbach, J; Friedman, J M (Genome Research, 1995)
The recently identified mouse obese (ob) gene apparently encodes a secreted protein that may function in the signaling pathway of adipose tissue. Mutations in the mouse ob gene are associated with the early development of gross obesity. A detailed knowledge concerning the RNA expression pattern and precise genomic location of the human homolog, the OB gene, would facilitate examination of the role of this gene in the inheritance of human obesity. Northern blot analysis revealed that OB RNA is present at a high level in adipose tissue but at much lower levels in placenta and heart. OB RNA is undetectable in a wide range of other tissues. Comparative mapping of mouse and human DNA indicated that the ob gene is located within a region of mouse chromosome 6 that is homologous to a portion of human chromosome 7q. We mapped the human OB gene on a yeast artificial chromosome (YAC) contig from chromosome 7q31.3 that contains 43 clones and 19 sequence-tagged sites (STSs). Among the 19 STSs are eight corresponding to microsatellite-type genetic markers, including seven (CA)n repeat-type Genethon markers. Because of their close physical proximity to the human OB gene, these eight genetic markers represent valuable tools for analyzing families with evidence of hereditary obesity and for investigating the possible association between OB mutations and human obesity.